2019
DOI: 10.1590/1413-82712019240205
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of behavioral problems in adolescents: family, personal and demographic variables

Abstract: This study aimed to correlate, compare and identify the family, personal and demographic variables that may predict behavioral problems in adolescents. A total of 300 adolescents participated, 230 with behavioral problems (177 girls and 53 boys; M= 14.00 years; SD=1.24) and 70 without (47 girls and 23 boys; M=14.09 years; SD=1.33). Data was collected through questionnaires and inventories completed by adolescents and analyzed using Pearson’s correlation, Student’s t-tests and multiple binary logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
8
0
3
Order By: Relevance
“…Multiple factors can influence school performance, among them stand factors related to the student itself, their school context and their family environment (SSF). Genetic and epigenetic factors collaborate in the expression and development of cognitive and social skills throughout life (Briley et al, 2018); the student's level of anxiety and their sense of well-being is related to their grades in the assessments (Gonzaga, Silva & Enumo, 2017;Stein & Nesse, 2015;Steinmayr, Crede, McElvany & Wirthwein, 2016); the student's level of curiosity and responsiveness to take initiatives, and their tendency to engage in individual and group activities collaborate with his performance at school (Fogaça, Tatmatsu, Comodo, Del Prette & Del Prette, 2019); and on the other hand, impulsiveness, distraction, the inability to postpone gratifications, and the readiness to resort to aggression and violence are disruptive characteristics that can hinder educational relationships and achievements (Campos, Silva, Zanini & Loureiro, 2019;Fogaça et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors can influence school performance, among them stand factors related to the student itself, their school context and their family environment (SSF). Genetic and epigenetic factors collaborate in the expression and development of cognitive and social skills throughout life (Briley et al, 2018); the student's level of anxiety and their sense of well-being is related to their grades in the assessments (Gonzaga, Silva & Enumo, 2017;Stein & Nesse, 2015;Steinmayr, Crede, McElvany & Wirthwein, 2016); the student's level of curiosity and responsiveness to take initiatives, and their tendency to engage in individual and group activities collaborate with his performance at school (Fogaça, Tatmatsu, Comodo, Del Prette & Del Prette, 2019); and on the other hand, impulsiveness, distraction, the inability to postpone gratifications, and the readiness to resort to aggression and violence are disruptive characteristics that can hinder educational relationships and achievements (Campos, Silva, Zanini & Loureiro, 2019;Fogaça et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the school context that affects performance includes teacher training (Prates, Lima & Ciasca, 2016), the pedagogical and political project and the curriculum (Dessotti & Dessotti, 2015), the climate (Melo, 2017), the physical structure of the school (Miranda, Pereira & Rissetti, 2016), the teacher-student relationship (Campos et al, 2019;Pezzi & Marin, 2017), among others. The bioecological approach to human development establishes the importance of the school in the development of the student, as a context of the life cycle, since it is where young people spend two decades of their lives (Bronfenbrenner & Morris, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between parents 3 and their children 4 and their repercussions on human development trajectories constitute a complex phenomenon, since they involve the interplay between multiple variables, such as personal characteristics, sociodemographic conditions of families, and broader sociocultural context in which the family lives. In order to understand the impacts of the context of parenting on the development process of children and adolescents, studies have shown the association between parenting practices and developmental outcomes Borden et al, 2014;Campos, 2019;Sabbag & Bolsoni-Silva, 2015;Trepat et al, 2014), indicating the need for protective government actions, focused on promoting health and preventing possible harm to human development (Coelho et al, 2020).…”
mentioning
confidence: 99%
“…However, negative parenting practices are associated with children's behavior problems Bolsoni-Silva et al, 2016;Borden et al, 2014;Campos, 2019;Magnani & Staudt, 2018;Trepatet al, 2014) and the use of Psychoactive Substances (PAS) in adolescence (Valente et al, 2017). In this sense, high frequencies of neglect, authoritarianism, and physical abuse are associated with the growing vulnerability of adolescents in relation to drug abuse (Valente et al, 2017).…”
mentioning
confidence: 99%
“…Correlações negativas foram identificadas entre problemas de comportamento e HSE-P(Assis & Bolsoni-Silva, 2020;Sabbag & Bolsoni-Silva, 2011), habilidades sociais infantis e práticas negativas(Sabbag & Bolsoni-Silva, 2011) e problemas de comportamento e habilidades sociais da criança(Assis & Bolsoni-Silva, 2020;Boas & Bolsoni-Silva, 2010;Sabbag & Bolsoni-Silva, 2011;Rovartis & Bolsoni-Silva, 2020). Tais resultados indicam que o uso do RE-HSE-P se mostrou eficaz para mensurar as interações entre pais e filhos(Fogaça & Bolsoni-Silva, 2018).Há vasta literatura evidenciando que os comportamentos habilidosos dos pais, isto é, a presença de habilidades sociais educativas promove habilidades sociais, reduzindo os problemas de comportamento infantisCampos, Bolsoni-Silva, Zanini, & Loureiro, 2019;Del Prette & Del Prette, 2008;Leme & Bolsoni-Silva, 2010;Marturano, 1999; Rovaris & Bolsoni-Silva, 2020). Em oposição, o uso de práticas educativas negativas (ausência de HSE) pode diminuir comportamentos habilidosos e favorecer o surgimento e a manutenção de problemas de comportamento D'Ávila-Bacarji, Marturano, & Elias, 2005;Boas & Bolsoni-Silva, 2010;, Assis & Bolsoni-Silva, 2020.…”
unclassified